A new elasmosaurid (Sauropterygia, Plesiosauria) from the Bearpaw Shale (Late Cretaceous, Maastrichtian) of Montana demonstrates multiple evolutionary reductions of neck length within Elasmosauridae - Serratos, D; Druckenmiller, P; Benson, R (Society of Vertebrate Paleontology, 2017)
Plesiosauria is a diverse clade of marine reptiles that have been studied since the early 19th century. However, phylogenetic relationships within the group have been contentious due to limited taxon sampling and a misunderstanding of how ontogeny, interspecific and intraspecific variation affect character states. This is particularly true for elasmosaurids, a Cretaceous clade of long-necked plesiosaurians. In 2010, a new, nearly complete skeleton, MOR 3072, was collected from the Late Cretaceous (Campanian–Maastrichtian) Bearpaw Shale of northeast Montana. The specimen provides detailed morphological information rarely observed within Elasmosauridae, including a complete skull, the anterior 23 cervical vertebrae, a partial dorsal and caudal vertebral column, incomplete pectoral and pelvic girdles, elements of both fore- and hind limbs, ribs, and gastralia. Being early Maastrichtian in age, MOR 3072 is the stratigraphically youngest elasmosaurid known from the Western Interior Seaway, and is recognized as a new genus and species, Nakonanectes bradti. We present a description of N. bradti and conduct an extended phylogenetic analysis of Elasmosauridae. N. bradti is found to be deeply-nested within the clade of large-bodied, long-necked, Western Interior Styxosaurinae. However, MOR 3072 is one of the smallest adult elasmosaurids ever recovered (5.1–5.6 m) and exhibits a reduced neck length compared to other North American elasmosaurids, resulting from a reduction in both centrum length and number of cervical vertebrae (39–42 were originally present). These features are convergent with the Southern Hemisphere clade of short-necked Maastrichtian elasmosaurids, Aristonectinae, and demonstrate multiple origins of shortnecked body proportions from longer-necked ancestors within Elasmosauridae.